Analisis Kesiapan Guru dalam Menghadapi Asesmen Kompetensi Minimum (Studi Kasus di SD Negeri Gemah Satuan Pendidikan Kecamatan Pedurungan Kota Semarang) - Widyastuti, Nora; Purnamasari, Iin; Sumarno, Sumarno (Universitas PGRI Semarang, 2023)
The dynamics of the development of national education in the Republic of Indonesia always experiences policy changes. Indonesia has at least experienced more than ten changes in curriculum development since the beginning of independence The National Assessment as a substitute for the National Exam has the aim of producing information about students, then the student information is used by educators to improve the quality of teaching and learning activities. This study used a descriptive qualitative approach, collecting data using interviews, observation and documentation. The primary data source was interviews with teacher informants and the secondary sources were observation and documentation. Based on the results of the study, namely: 6 (six) of the teachers at SDN Gemah, 4 (four teachers) were ready to face AKM. This can be seen from: Knowledge about AKM, Ability to identify AKM questions, teacher's understanding of the IKM concept; Activeness in education and training, making strategies and learning methods for the independent curriculum and supporting learning media, implementing AKM materials for students. Meanwhile, 2 (two) teachers were not ready to face AKM. This can be seen from: Lack of knowledge about AKM, Lack of ability to identify AKM questions, Lack of teacher understanding of the AKM concept; There is no initiative to take part in AKM training and training, less able to make independent curriculum learning strategies and methods, lack of mastery of using IT, unable to make learning media for independent curriculum and unable to implement AKM material to students.